1998
DOI: 10.1073/pnas.95.10.5746
|View full text |Cite
|
Sign up to set email alerts
|

Host cell dependence of viral morphology

Abstract: The morphology of inf luenza virions was found to depend on cellular determinants. Inf luenza viral filaments up to 30 m in length were observed to form at high levels on surfaces of various polarized epithelial cell types infected with the A͞Udorn͞72 virus. In contrast, virions produced by nonpolarized cell types infected with this virus were almost exclusively of spherical morphology. Disruption of the actin microfilament array by cytochalasin D treatment of polarized MDCK cells had a profound effect on vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
117
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 39 publications
9
117
1
Order By: Relevance
“…Cellular factors associated with the vacuolar sorting pathway are implicated in virus budding and release for several virus families, and some of these may form protein assemblies that regulate the physical constriction required for pinching-off (38). It is not known what host factors regulate orthomyxovirus budding (39,40), but host factors such as actin and the virus M2 protein may contribute to the filamentous phenotype (20,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular factors associated with the vacuolar sorting pathway are implicated in virus budding and release for several virus families, and some of these may form protein assemblies that regulate the physical constriction required for pinching-off (38). It is not known what host factors regulate orthomyxovirus budding (39,40), but host factors such as actin and the virus M2 protein may contribute to the filamentous phenotype (20,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cytochalasin D has an effect on viral internalization, assembly, and budding of influenza A virus in a virus strain-and cell polarity-dependent manner (31)(32)(33). Therefore, we first examined the effect of cytochalasin D on the expression of influenza proteins.…”
Section: An Intact Actin Cytoskeleton Is Essential For Full Expressiomentioning
confidence: 99%
“…The surfaces of infected cells are covered by large clumps of filamentous protrusions, which can be visualized by light microscopy, immunofluorescence staining, and electron microscopy (2, 3, 35, 51). The morphology of budding virions depends on cellular determinants such as polarized cell phenotype and the integrity of the actin microfilament network (6,39). The determinants of RSV's spherical and filamentous morphological forms and the roles of such particles in virus transmission and pathogenicity are not clearly defined.…”
mentioning
confidence: 99%